HUBUNGAN TINGKAT PENGETAHUAN ASUPAN GIZI DAN KEPATUHAN DIET DENGAN KADAR GULA DARAH PASIEN DIABETES MELLITUS - Kusuma Wardani, Dyah Ayu; Al Rahmad, Agus Hendra; Lestari, Dwi; Anshory, Jamil; Utami, Kurniati Dwi (Ensiklopedia of Journal, 2024)
Knowledge of the diabetes mellitus diet is the first step in increasing compliance of diabetic patients regarding their dietary patterns. Compliance of diabetes patients in implementing a diet is the main key to the stability of the health condition of diabetes mellitus patients. Compliance in diet is one of the factors to stabilize blood sugar levels to normal and prevent complications. This study aims to see the relationship between the level of knowledge of nutritional intake and dietary compliance with blood sugar levels of patients with diabetes mellitus at the Kampar Kiri Hilir Health Center. This research design is an analytic observation with a cross sectional research design where researchers analyze the relationship between knowledge and dietary compliance with blood sugar levels of patients with Diabetes Mellitus at Puskesmas Kampar Kiri Hilir. Instruments in data collection using research questionnaires. The sample in this study were 100 people. Data were analyzed using the Mann Whitney test. The results of this study found that knowledge of nutritional intake with blood sugar levels of diabetics obtained p value = 0.996 and diet compliance with blood sugar levels of diabetics obtained p value = 0.606. Suggestions from this study are that the Puskesmas should be more active in educating the community regarding control and control of blood sugar.Keywords: Knowledge, Nutrition Intake, Adherence, Diabetes Mellitus